GAMBARAN KEJADIAN HIPOTERMIA, MUAL DAN MUNTAH POST OPERASI DENGAN GENERAL ANESTESI DI RS JATIWINANGUN PURWOKERTO - Rumantika Rumantika; Made Suandika; Rahmaya Nova Handayani (Jurnal Inovasi Penelitian, 2022)
General anesthesia is a procedure that aims to relieve pain, cause unconsciousness, and memory loss that is reversible and predictable. A possible complication after anesthesia is hypothermia. Complications of hypothermia from general anesthesia surgery are Post Operative Nausea and Vomiting (PONV). The purpose of this study was to describe the incidence of hypothermia, postoperative nausea and vomiting under general anesthesia at Jatiwinangun Hospital, Purwokerto. The research method used quantitative observational descriptive cross-sectional research design. The research site is at IBS Jatiwinangun Hospital, Purwokerto. The time of the study was 12 July – 10 August 2022. The study population consisted of all patients who underwent surgery under general anesthesia in the IBS room at Jatiwinangun Hospital Purwokerto an average of 142 people each month, and the number of samples was 36 using consecutive sampling technique. Instruments in the form of a digital thermometer and observation sheets. Data analysis in the form of univariate explains the frequency distribution and percentage of each variable. The results of the study were the incidence of hypothermia with general anesthesia from 36 respondents. Most of the respondents experienced moderate hypothermia (temperature 28-320C) as many as 21 respondents (58.3%). The incidence of PONV with general anesthesia from 36 respondents obtained that the majority of respondents experienced PONV as many as 23 respondents (63.9%). In conclusion, most of the respondents experienced moderate hypothermia (58.3%) and experienced PONV (63.9%).